Architecting Hierarchical WO3 Agglomerates Assembled With Straight and Parallel Aligned Nanoribbons Enabling High Capacity and Robust Stability of Lithium Storage - Dong, Xiaotong; Liu, Yongshuai; Zhu, Shikai; Ou, Yike; Zhang, Xiaoyu; Lan, Wenhao; Guo, Haotian; Zhang, Cunliang; Liu, Zhaoguo; Ju, Shuai; Miao, Yuan; Zhang, Yongcheng; et al. (Frontiers in Chemistry, 2022)
The pursuit of electrochemical energy storage has led to pressing need on materials with high capacities and energy densities, however, the further progress is plagued by the restrictive capacity (372 mAh g-1) of conventional graphite materials. Tungsten trioxide (WO3)-based anodes feature high theoretical capacity (693 mAh g-1), suitable potential, and affordable cost, arousing ever-increasing attention and intense efforts. Nonetheless, daunting challenge remains for developing high-performance WO3 electrodes accommodating lithium ions on account of sluggish kinetics characteristics and large volume strain. Herein, the well-designed hierarchical WO3 agglomerates assembled with straight and parallel aligned nanoribbons are fabricated and evaluated as an anode of lithium-ion batteries (LIBs), which exhibits an ultra-high capacity and excellent rate capability. At a current density of 1000 mA g-1, a reversible capacity as high as 522.7 mAh g-1 can be maintained after 800 cycles, corresponding to a high capacity retention of ~80%, demonstrating an exceptional long-durability cyclic performance. Furthermore, the mechanistic studies on the lithium storage processes of WO3 are probed, providing a foundation for further optimizations and rational designs. These results indicate that the well-designed hierarchical WO3 agglomerates display great potential for applications in the field of high-performance LIBs.